Synthesis and characterization of curcumin loaded polymer/lipid based nanoparticles and evaluation of their antitumor effects on MCF-7 cells - Kumar, Sathish Sundar Dhilip; Mahesh, Ayyavu; Mahadevan, Surianarayanan; Mandal, Asit Baran (Biochimica et biophysica acta, 2014)
Hybrid materials are synthesized using hydrophilic polymer and lipids which ensure their long term systemic circulation through intravenous administration and enhance loading of hydrophobic drugs. The purpose of this study is to prepare, characterize and evaluate the in vitro efficacy of curcumin loaded poly-hydroxyethyl methacrylate/stearic acid nanoparticles in MCF-7. C-PSA-NPs, prepared using the emulsification-solvent evaporation method were characterized by dynamic laser scattering, SEM, AFM, FT-IR, X-ray diffraction, and TGA. The in vitro release behavior was observed in PBS pH7.4, the anticancer potential was analyzed by MTT assay, cell cycle and apoptosis studies were performed through flow cytometry. C-PSA-NPs drug localization and cancer cell morphological changes were analyzed in MCF-7 cell line. C-PSA-NPs exhibited the mean particle size in the range of 184nm with no aggregation. The surface charge of the material was around -29.3mV. Thermal studies (TGA) and surface chemistry studies (FT-IR, XRD) showed the existence of drug curcumin in C-PSA-NPs. The MTT assay indicated higher anticancer properties and flow cytometry studies revealed that there were better apoptotic activity and maximum localization of C-PSA-NPs than curcumin. Polymer lipid based drug delivery appeared as one of the advancements in drug delivery systems. Through the present study, a novel polymer lipid based nanocarrier delivery system loaded with curcumin was demonstrated as an effective and potential alternative method for tumor treatment in MCF-7 cell line. C-PSA-NPs exhibited potent anticancer activity in MCF-7 cell line and it indicates that C-PSA-NPs are a suitable carrier for curcumin.